THIN FILM TRANSISTORS WITH InGaZnO-SEMICONDUCTOR LAYER FOR ACTIVE MATRIX ADDRESSING - B. A. Kazarkin; A. A. Stepanov; Y. U. Mukha; I. I. Zakharchenia; Y. A. Khakhlou; A. G. Smirnov (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The paper presents the results of a study of thin-film transistors based on the InGaZnO semiconductor compound (IGZO) for active-matrix displays addressing formed by magnetron plasma-chemical deposition. Their structural-morphological and electrophysical properties are investigated. Carrier mobility is analyzed using the Hall method. The effect of annealing in vacuum, an oxygen atmosphere, and a nitrogen atmosphere on the grain size of an IGZO film was investigated. The resulting layers are characterized by high mobility of charge carriers, which allows their use in the manufacture of new-generation LCD and OLED displays.